Coptotermes sp. (rhinotermitidae: Coptotermitinae) infestation pattern shifts through time in oil palm agroecosystem - Nur-Atiqah J.; Saputra A.; Mohammad Esa M.F.; Shafuraa O.; Billy A.N.A.; Mohd Yaziz N.A.A.; Faszly Rahim (Universiti Kebangsaan Malaysia Press, 2024)
Indexed by Scopus